Paris in love [compact disc, unabridged] : a memoir - James, Eloisa (Books on Tape, 2012)
In 2009, New York Times bestselling author Eloisa James took a leap that many people dream about. She sold her house, took a sabbatical from her job as a Shakespeare professor, and moved her family to Paris. Paris in Love chronicles her joyful year in one of the most beautiful cities in the world.